Minimum Leaf Conductance (gmin) Is Higher in the Treeline of Pinus uncinata Ram. in the Pyrenees: Michaelis’ Hypothesis Revisited - Bueno, Amauri; Alonso-Forn, David; Peguero-Pina, José Javier; de Souza, Aline Xavier; Ferrio, Juan Pedro; Sancho-Knapik, Domingo; Gil-Pelegrín, Eustaquio (Frontiers in Plant Science, 2022)
Sub-alpine forest transition to the alpine tundra is formed by the forest mass opening, leading to isolated specimens, which become progressively stunted, culminating in prostrate individuals, called Krummholz. The search for a universal explanation of this altitudinal limit determined by the alpine treeline has given rise to different hypotheses. In this study, we revisited Michaelis’ hypothesis in which proposed that an inadequate “ripening” of the cuticle caused a greater transpiration rate during winter in the treeline. However, few studies with seemingly contradictory results have investigated the role of passive mechanisms of needles for protecting against water loss during winter in conifers at the treeline. To shed light on this, the cuticular transpiration barrier in the transition from subalpine Pinus uncinata forests to alpine tundra in the upper limit of the species in the Pyrenees was studied as an example of the ecotones formed by conifers in the temperate mountains of the northern hemisphere. Our study showed that minimum leaf conductance in needles from upper limit specimens was higher than those measured in specimens living in the lower levels of the sub-alpine forest and also displayed lower cuticle thickness values, which should reinforce the seminal hypothesis by Michaelis. Our study showed clear evidence that supports the poor development of needle cuticles as one of the factors that lead to increased transpirational water losses during winter and, consequently, a higher risk of suffering frost drought.